2019
DOI: 10.1016/j.addbeh.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Vaping for weight control: A cross-sectional population study in England

Abstract: Introduction Concern about weight gain is a barrier to smoking cessation. E -cigarettes may help quitters to control their weight through continued exposure to the appetite-suppressant effects of nicotine and behavioural aspects of vaping. This study explored the views and practices of smokers, ex-smokers and current e-cigarette users relating to vaping and weight control. Methods Cross-sectional survey of past-year smokers ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Additionally, EC use was believed to aid weight control among the respondents in our study, and no significant differences were found between dual and single users in the appetite/weight control scale. This is similar to the findings of several studies, including a study in the United Kingdom which reported that e-cigarettes are often used to replace a meal or a snack [ 41 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, EC use was believed to aid weight control among the respondents in our study, and no significant differences were found between dual and single users in the appetite/weight control scale. This is similar to the findings of several studies, including a study in the United Kingdom which reported that e-cigarettes are often used to replace a meal or a snack [ 41 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…21,31 This concern also involves whether e-cigarette use is gateway for people seeking to control their weight. 19,32 Given this interest, it is essential to emphasize that nicotine has many deleterious effects on health in addition to its possible effects on weight. High nicotine concentrations can cause acute toxicity, increasing the risk of disease by activating multiple biological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Massive public health campaigns have addressed the need for smoking cessation and proposed pharmacological and behavioral interventions that help smokers to quit. However, an enduring concern of smokers is weight gain after abstaining from cigarettes, 19 especially among females 20 . Thus, some studies have reported e‐cigarettes may serve as a smoking cessation aid 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys show that many quitters are not aware of potential weight benefits with use of nicotine e-cigarettes [53,63]. The quit rate especially in people with diabetes is low, and whether the awareness of weight benefit could improve quit rates remains to be shown.…”
Section: E-cigarette Smokingmentioning
confidence: 99%
“…The quit rate especially in people with diabetes is low, and whether the awareness of weight benefit could improve quit rates remains to be shown. A survey of English smokers concluded that one in eight people would stop smoking if they were convinced that vaping prevented gain weight [63]. Several studies on vaping in regards its weight benefit are ongoing, and some researchers discuss nicotine vaping as intervention for the management of obesity per se [63][64][65].…”
Section: E-cigarette Smokingmentioning
confidence: 99%